The Influence Of Respiratory Relaxation Techniques On Pain Intensity In The First Stage Of Labor At The Atikah Sipolu-Polu Midwifery Clinic, Panyabungan District, Mandailing Natal Regency - Khourinisa, Khourinisa; Helmi Wardah Nasution (Sean Institute, 2022)
Pain is a part that is always present in the birthing process. The discomfort and pain felt during the labor process is the cause of prolonged labor. Non-pharmacological therapies that can be given to reduce pain include breathing relaxation techniques. The aim of this research is to determine the effect of respiratory relaxation on pain intensity in the first stage of labor at the Atikah Midwife Clinic in 2022. This research is a quantitative research method with a one group pre-test and post-test design. The sample in this study was approximately 10 mothers giving birth at the Atikah Midwife Clinic. The research instrument used was a questionnaire using the numeric rating scale (NRS). The results of the study showed that the intensity of pain in the first stage of labor after being given treatment was lower than the level of pain before being given breathing relaxation techniques, indicated by median values of 3 and 7.5 respectively. Before treatment was given, the highest pain level was a score of 9 (severe pain) and the lowest was a score of 5 (moderate pain). Meanwhile, after being given breathing relaxation technique treatment, the highest level of pain was a score of 6 (moderate pain) and the lowest was a score of 2 (mild pain). The results of statistical tests using the Wilcoxon Test showed that the p value (0.004) < α (0.05) means Ho is rejected, so there is a difference in reducing pain in the first stage of labor before and after the breathing relaxation technique. These results prove that there is a significant effect of respiratory relaxation on reducing pain in the first stage of labor at the Atikah Sipolu-Polu Midwife Clinic, Panyabungan District, Mandailing Natal Regency in 2022. These results prove that breathing relaxation techniques can reduce pain in the first stage of labor.